Climb the family tree, Jesse Bear! - Carlstrom, Nancy White (Simon & Schuster Books for Young Readers, 2004)
Jesse Bear experiences the excitement of a family reunion filled with grandparents, aunts, uncles, and cousins and lots of food, games, and storytelling.